2006
DOI: 10.1007/s11104-006-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single Chinese Fir and Mixed Leaf Litters on Soil Chemical, Microbial Properties and Soil Enzyme Activities

Abstract: The quality of leaf litter can control decomposition processes and affect the nutrient availability for plant uptake. In this study, we investigated the effect of single leaf litter (Chinese fir -Cunninghamia lamcealata (Lamb.) Hook) and mixed leaf litters (C. lamcealata, Liquidamba formosana Hance and Alnus cremastogyne

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 28 publications
(31 reference statements)
2
38
0
Order By: Relevance
“…Compared with the single-species Pr litter treatment, the Pr + Cj treatment significantly increased soil MBC by 10.6, 18.4 and 25.7%, and the Pr + Od treatment significantly increased it by 14.7, 20.6 and 30.5% at day 14, 42 and 84, respectively (P < 0.05). The increasing substrate availability underlying the mixed leaf litters may contribute to the increase of soil MBC, which was also observed in the other studies on soil microbial properties responding to the litter mixtures (Hu et al 2006).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Compared with the single-species Pr litter treatment, the Pr + Cj treatment significantly increased soil MBC by 10.6, 18.4 and 25.7%, and the Pr + Od treatment significantly increased it by 14.7, 20.6 and 30.5% at day 14, 42 and 84, respectively (P < 0.05). The increasing substrate availability underlying the mixed leaf litters may contribute to the increase of soil MBC, which was also observed in the other studies on soil microbial properties responding to the litter mixtures (Hu et al 2006).…”
Section: Resultssupporting
confidence: 77%
“…The activities of the enzymes, intracellular dehydrogenase and extracellular β-glucosidase, were measured according to the methods given by Guan (1986). Detailed method of determining soil dehydrogenase activity was described by Hu et al (2006). Dehydrogenase activity was expressed in μg triphenyl formazan (TPF) released/g dry soil/h.…”
Section: Soil Microbial Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies report that build-up of plant pathogens is one of the major causes in soil sickness in Cistus ladanifer (Hassan et al, 1989), peach (Benizri et al, 2005), cucumber (Yao et al, 2006), Rehmannia glutinosa (Chen et al, 2007), Liriope (Zhao et al, 2010), while autotoxicity has been reported to be one of the major causes in soil sickness in cucurbit crops (Yu et al, 2000), alfalfa (Segiun et al, 2002), Cistus ladanifer (Alías et al, 2006), cucumber (Yao et al, 2006) and wheat (Wu et al, 2007). In many cases, soil microorganism played either direct or indirect role in yield reduction (Manici et al, 2003;Hu et al, 2006). In conclusion, the cause of soil sickness is complex.…”
Section: Introductionmentioning
confidence: 99%